Natatorium, Interior: Swimming Pool (1938)
Label on front: 'Indoor swimming pool, 75 feet long and 35 feet wide. Adjacent to the locker and shower rooms of the gymnasium, the pool is complete with heating, filtration and chlorinating equipment and has a spectator gallery seating 300 persons.'